A randomized, phase 2 study of ASP0113, a DNA‐based vaccine, for the prevention of CMV in CMV‐seronegative kidney transplant recipients receiving a kidney from a CMV‐seropositive donor. Issue 12 (20th June 2018) - Vincenti, Flavio; Budde, Klemens; Merville, Pierre; Shihab, Fuad; Ram Peddi, V.; Shah, Malay; Wyburn, Kate; Cassuto‐Viguier, Elisabeth; Weidemann, Alexander; Lee, Misun; Flegel, Teresa; Erdman, Jay; et al.
Abstract : Cytomegalovirus (CMV) is a latent infection in most infected individuals, but can be pathogenic in immunocompromised kidney transplant recipients. ASP0113 is a DNA‐based vaccine for the prevention of CMV‐related mortality and end‐organ disease in transplant recipients. The efficacy, safety, and immunogenicity of ASP0113 was assessed in a phase 2, double‐blind, placebo‐controlled study in CMV‐seronegative kidney transplant recipients receiving a kidney from a CMV‐seropositive donor. Transplant recipients were randomized (1:1) to receive 5 doses of ASP0113 (5 mg; n = 75) or placebo (n = 74) on Days 30/60/90/120/180 posttransplant, and they received prophylactic valganciclovir/ganciclovir 10‐100 days posttransplant. The primary endpoint was the proportion of transplant recipients with CMV viremia ≥1000 IU/mL from Day 100 through to 1 year after the first study vaccine injection. There was no statistically significant difference in the primary endpoint between the ASP0113 and placebo groups (odds ratio 0.79, 95% confidence interval 0.43‐1.47; P  = .307). There were similar numbers of transplant recipients with treatment‐emergent adverse events between groups; however, more transplant recipients reported injection site pain in the ASP0113 group compared with placebo. ASP0113 did not demonstrate efficacy in the prevention of CMV viremia in this CMV‐seronegative kidney transplant population, but demonstrated a safety profile similar to placebo. ClinicalTrials.gov registration number: NCT01974206. Abstract : This phase 2 study demonstrates that ASP0113 has a safety profile similar to placebo, but is not effective for the prevention of cytomegalovirus viremia in cytomegalovirus‐seronegative kidney transplant recipients receiving a kidney from a cytomegalovirus‐seropositive donor. See Emery's comments onpage 2847 .